KAIDAH RASM á¸¤ADHF ALÃŽF DALAM MUSHAF STANDAR INDONESIA DAN MUSHAF KUNO KOLEKSI PONDOK PESANTREN TEBUIRENG - Adrika Fithrotul Aini (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This research describes about the model of using of the rule of rasm in hadhf and ithbat alif in three letters, namely the letter Yasin, al-Rahman, and al-Waqiâ€™ah. The object of this research study is the Indonesian standard Manuscripts (MSI) made by the Ministry of Religion and ancient Manuscripts in the Tebuireng Islamic Boarding School (MQT). Taking of these two Manuscripts is intended as the first step to see the development of using of the rasm in Manuscripts in Indonesia started from the ancient Manuscripts until the formation of Indonesian standard Manuscripts. From the results of the analysis of researchers in seeing the application of h}adhf and ithba>t alif rules on the two Manuscripts, it concludes that the Indonesian standard Manuscripts do the mixed rules in writing alif. While the ancient Manuscripts collection of Tebuireng Islamic boarding schools are more likely to make detrmaining alif (ithbat).